2016
DOI: 10.1111/jph.12511
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cassava Cultivars for Resistance to Cassava Mosaic Disease and Yield Potential in Central African Republic

Abstract: Eleven cassava genotypes were tested against cassava mosaic disease (CMD) and compared to a local susceptible cultivar in field conditions from June 2011 to July 2012 in Central African Republic (CAR) at two sites representative of the savanna (Damara) and forest (Pissa) zones of the country. The mean number of whiteflies observed on plants varied among genotypes within each site, but was found nearly three times higher at Damara than at Pissa, resulting in a CMD incidence nearly five times higher at Damara th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 25 publications
(73 reference statements)
3
7
0
2
Order By: Relevance
“…No relationship was found between whiteflies abundance and severity of the CMD symptoms, nor between whitefly abundance and incidence of the disease. This result agrees with some previous studies [1], [50] where no clear association between whitefly abundance and CMD symptom severity was observed.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…No relationship was found between whiteflies abundance and severity of the CMD symptoms, nor between whitefly abundance and incidence of the disease. This result agrees with some previous studies [1], [50] where no clear association between whitefly abundance and CMD symptom severity was observed.…”
Section: Discussionsupporting
confidence: 93%
“…The pressure of whiteflies populations was different in the three experimental locations. This agrees with results of Zinga et al (2016) [1], who found that populations of whiteflies mainly change with environmental conditions. No relationship was found between whiteflies abundance and severity of the CMD symptoms, nor between whitefly abundance and incidence of the disease.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…La culture du manioc comme pour toutes les plantes cultivées présentent des rendements très variables selon que les conditions du sol et du climat lui sont favorables ou défavorables (Tandzi et al, 2020). L'effet des fumiers et des termitières sur la croissance et le rendement du manioc et l'effet des régulateurs de croissance sur la culture in vitro du manioc étaient étudiés et documentés, ces facteurs sont importants pour la qualité de la culture Ballot et al, 2016 b). La culture du manioc dans le champ se fait plus par bouturage à partir d'un échantillon mur.…”
Section: Discussionunclassified
“…Cette technique nécessite plusieurs étapes qui peuvent être résumées en la phase d'initiation de culture in vitro et d'acclimatation sous serre avant le transfert en champ. Plusieurs cultivars de la RCA ont fait l'objet de culture in vitro permettant d'évaluer les conditions opératoires et les performances agronomiques en analysant le taux de survie, la taille, les racines et le nombre de feuilles (Zinga et al, 2016). Cependant, l'acclimatation des vitroplants à la sortie du laboratoire reste une étape difficile à maitriser et qui varie en fonction de la spécificité de chaque accession.…”
Section: Introductionunclassified